"Despite being an athlete, I am also a human-being": Male elite gymnasts` reflections on food and body image - Pinto, J.; Dolan, E.; Baldissera, G.; de Souza Gonçalves, L.; de Araújo Jardim, F. G.; Caruso Mazzolani, B.; Smaira, F. I.; de Morais Sato, P.; Baeza Scagliusi, F.; Gualano, B. (European Journal of Sport Science, 2020)
Our aim was to investigate the prevalence of symptoms related to eating disorders, disordered eating and body image perception, and attitudes toward eating in a group of elite male artistic gymnastics. Seventeen athletes took part in this quali-quantitative, cross-sectional study. Presence of eating disorders symptoms, and body image perception and satisfaction were assessed using validated questionnaires. Focus groups were held to discuss their attitudes toward eating and body image perception in more detail. Little to no evidence of symptoms consistent with eating disorders was observed, and this was supported by the qualitative data. However, some concerning practices and attitudes were described. Negative emotional eating cycles appeared prevalent (e.g. feelings of anger, stress and anxiety creating a desire to eat "junk foods", followed by guilt and regret). Body image perception and attitudes toward body weight`s influence on performance varied widely. Some athletes expressed a desire to lose weight and believed that this would positively impact their performance, while others believed weight to be irrelevant and focused on feeling strong and vital. Athletes believed their female counterparts experienced far greater pressure to maintain low body weight and described some very concerning practices. We conclude that eating disorders and disordered eating did not appear to be prevalent among these elite male artistic gymnastics. However, some concerning attitudes and practices were observed and should be addressed with nutritional support programmes encompassing psychological and behavioural aspects of eating. These programmes should be extended to support staff and significant others, in addition to athletes.